A study on the dynamics of international migration between the Governador Valadares Microregion and the United States, 2000-2010 - de Sousa, Leonardo Gomes (2016)
The microregion of Governador Valadares (MGV) is the most representative Brazilian regional area regarding out-migration of Brazilians to the United States. However, in the 2000 decade, new and adverse global changes that economically would affect both the origin and destination settings implying in a probable reduction or even a complete interruption of out-migration flows. This paper aims to analyze the hypothesis that, even in an apparent adverse scenario, international out-migration continued with considerable intensity during the first half of the 2000 decade. The formation of the international out-migration flows from the MGV to the USA and its adherence to the migration theories was analyzed, and also provided an empirical investigation considering the stocks and flows of international migrants within the Brazil-USA migration system. The results show that in the 2000’s the structured migration system, based and reinforced by the personal migration networks in the region, exerted a considerable force towards the regulation of the out-migration flows.